Technology competition and regulatory advantage - Ralf Boscheck (Intereconomics, 2010)
The importance of competition law as a policy lever to help the EU compete at the forefront of science and technology seems to have been overlooked by the Commission. As a consequence, the EU appears to be at a disadvantage to the USA in terms of the regulatory environment for intellectual property and licensing practices. This article examines these differences and explores the pros and cons of the European and American approaches to competition law, ultimately arguing in favour of regulatory harmonisation.
Keywords: 330